Nutrition of children and women in Bangladesh: trends and directions for the future - Ahmed, Tahmeed; Mahfuz, Mustafa; Ireen, Santhia; Ahmed, A. M. Shamsir; Rahman, Sabuktagin; Islam, M Munirul; Alam, Nurul; Hossain, Md Iqbal; Rahman, S M Mustafizur; Ali, M Mohsin; Choudhury, Fatima Perveen; Cravioto, Alejandro (© 2012 Journal of Health, Population and Nutrition, 2017)
This review was published in the Journal of Health, Population and Nutrition [© 2012 © International Centre for Diarrhoeal Disease Research, Bangladesh] and the definite version is available at : https://www.ncbi.nlm.nih.gov/pmc/articles/PMC3312353/